2006
DOI: 10.1016/j.visres.2005.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of binocular and monocular distractors on saccades in participants with normal binocular vision

Abstract: We tested the effect of visual distractors presented monocularly and binocularly on saccade latency and accuracy to determine whether differences occur in saccadic planning with binocular or monocular visual input. For five participants with normal binocular single vision (BSV), saccade latency and accuracy were compared with distractors presented to the dominant eye, non-dominant eye or to both eyes. Eye movements of the dominant eye were recorded using a Skalar infra-red recorder. In the presence of normal B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…An irrelevant stimulus (often called a "distractor") generally delays the intended saccade and can sometimes entirely "capture" the saccade, so that it is directed toward the distractor, not the target. Such delays and errors are often referred to as the oculomotor distractor effect, remote distractor effect (RDE, because the distractor is remote from the target), or oculomotor capture and have been widely used as measures of sensorimotor competition and interference in the eye movement system (e.g., Born and Kerzel 2008a;Graupner et al 2007;Griffiths et al 2006;Honda 2005;Lévy-Schoen 1969;Ludwig et al 2005;Theeuwes 1994;Theeuwes et al 1998;Walker et al 1995Walker et al , 1997White et al 2005). Here we refer to the slowing of latency to the target as the "RDE" (or simply the distractor effect) and refer to saccades toward the distractor as "capture.…”
Section: Sensorimotor Competition and The Oculomotor Distractor Effectmentioning
confidence: 99%
“…An irrelevant stimulus (often called a "distractor") generally delays the intended saccade and can sometimes entirely "capture" the saccade, so that it is directed toward the distractor, not the target. Such delays and errors are often referred to as the oculomotor distractor effect, remote distractor effect (RDE, because the distractor is remote from the target), or oculomotor capture and have been widely used as measures of sensorimotor competition and interference in the eye movement system (e.g., Born and Kerzel 2008a;Graupner et al 2007;Griffiths et al 2006;Honda 2005;Lévy-Schoen 1969;Ludwig et al 2005;Theeuwes 1994;Theeuwes et al 1998;Walker et al 1995Walker et al , 1997White et al 2005). Here we refer to the slowing of latency to the target as the "RDE" (or simply the distractor effect) and refer to saccades toward the distractor as "capture.…”
Section: Sensorimotor Competition and The Oculomotor Distractor Effectmentioning
confidence: 99%
“…For the case of remote distractors, Walker et al (1997) found an inverse relationship between the magnitude of the effect (or the saccade-latency increase in distractor compared to no-distractor trials) and the ratio of distractor-to-target eccentricity, which may support the fixation-system hypothesis. The distractor effect was greatest when the distractor was displayed at the center of the fovea, and then gradually reduced as the distractor was presented more peripherally and its eccentricity more closely matched the eccentricity of the target (see also Griffiths, Whittle, & Buckley, 2006). However, since this result relied on manipulation of the eccentricity of the distractor for only two possible target eccentricities, it may have been in part an effect of the angular distance between the stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…In psychophysics, saccades are studied both using monocular and binocular setups but we have not found in the literature a comparison of their accuracies. Some studies report that the presence of a monocular vs binocular distractor has different effects on the saccade accuracy, so showing that binocular information is used when available (Griffiths et al, 2006). Moreover, verifying the actual performance of monocular encoding with the robot allows us to predict the quality of saccades and perception in the case of occlusions, and also evaluate the opportunity of consistently employing a more demanding binocular processing.…”
Section: Discussionmentioning
confidence: 99%